RATIONALIZATION OF ADOPTION OF DISTANCE LEARNING IN POSTGRADUATE PEDAGOGICAL EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
In the article the reasonability of rationalization of distance learning adoption in the institutes of postgraduate pedagogical education was analyzed and found.
Keywords: distance education; distances learning systems; postgraduate pedagogical education; rationalization